Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Keterikatan Karyawan (Employee Engagemnent) Pada PT. Tokai Kagu Indonesia, Bekasi - Setiatun Wahyuningsih; Acep Rohendi; Wiseto P. Agung (STIE Trisna Negara OKU Timur, 2022)
This study aims to analyze the influence of leadership style and organizational culture on employee engagement at PT. Tokai Kagu Indonesia, either partially or simultaneously. The population in this study were all permanent employees of PT. Tokai Kagu Indonesia, Bekasi, found 216 people. Sampling of 68 people. Data were collected using a questionnaire, the measurement scale used a Likert scale. In data analysis using multiple linear regression test with SPSS 20 program. From the results of data analysis, it is known that the leadership style variable affects employee engagement by 30.2%. Organizational culture variables affect employee engagement by 77.5%. The determination test (R2) shows that the independent variables (leadership style and organizational culture) have a strong influence on the dependent variable by 66,2%, while 33,8 % is influenced by other factors. This means that improving the leadership style and organizational culture will increase employee engagement with the company so that company goals can be achieved.